Mammary Analog Secretory Carcinoma of the Nasal Cavity Characterization of 2 Cases and Their Distinction From Other Low-grade Sinonasal Adenocarcinomas - Baneckova, Martina; Agaimy, Abbas; Andreasen, Simon; Vanecek, Tomas; Steiner, Petr; Slouka, David; Svoboda, Tomas; Miesbauerova, Marketa; Michal, Michael; Skalova, Alena (American Journal of Surgical Pathology, 2018)
Secretory carcinoma, originally described as mammary analog secretory carcinoma (MASC), is a low-grade salivary gland tumor characterized by a t(12;15)(p13;q25) translocation, resulting in an ETV6-NTRK3 gene fusion. Most MASCs are localized to the parotid gland and intraoral minor salivary glands. Moreover, ETV6-rearranged carcinomas with secretory features have been reported recently in the thyroid (with and without a history of radiation exposure), skin, and in very rare instances in the sinonasal tract. Here, we describe 2 cases of primary MASC in the sinonasal tract and provide a detailed clinical and histopathologic characterization of their morphology, immunohistochemical profile, and genetic background and highlight features allowing for its separation from its recently described molecular mimicker, ETV6-rearranged low-grade sinonasal adenocarcinoma.
EVALuna2:34876